2003
DOI: 10.1007/s00467-003-1196-z
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of theophylline administration in tacrolimus-induced nephrotoxicity in rats

Abstract: Tacrolimus (TAC), a widely used nephrotoxic calcineurin inhibitor, is associated with renal vasoconstriction possibly through adenosine receptor activation. Theophylline (THEO), an adenosine receptor inhibitor, protects against the nephrotoxicity of drugs associated with renal vasoconstriction. We hypothesized that coadministration of low dose THEO in rats would prevent TAC-induced nephrotoxicity. Sprague-Dawley rats pair-fed a low-sodium diet were randomized into three groups ( n=10/group): the control (CONTR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…Furthermore, the acute reduction of GFR and renal blood flow caused in rats by a single dose of tacrolimus was completely reversed by theophylline given 1 hour after the drug (McLaughlin et al 2003a). Concomitant chronic administration of theophylline together with tacrolimus prevented the decrease of creatinine clearance that was caused by tacrolimus in the control group (McLaughlin et al 2003b). In contrast, chronic administration of theophylline did not protect against cyclosporine-induced renal failure in rabbits and even enhanced its cytotoxic effects whereas functional recovery was seen when theophylline was given as a single dose following a 5 day treatment with cyclosporine (Prevot et al 2002).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%
“…Furthermore, the acute reduction of GFR and renal blood flow caused in rats by a single dose of tacrolimus was completely reversed by theophylline given 1 hour after the drug (McLaughlin et al 2003a). Concomitant chronic administration of theophylline together with tacrolimus prevented the decrease of creatinine clearance that was caused by tacrolimus in the control group (McLaughlin et al 2003b). In contrast, chronic administration of theophylline did not protect against cyclosporine-induced renal failure in rabbits and even enhanced its cytotoxic effects whereas functional recovery was seen when theophylline was given as a single dose following a 5 day treatment with cyclosporine (Prevot et al 2002).…”
Section: Disease and Therapeutic Aspectsmentioning
confidence: 99%
“…It is plausible that prevention of renal ischaemia can delay renal failure; however, there is conflicting available data. Several authors demonstrated that while acute non-specific adenosine receptor antagonism with theophylline may prevent renal vasoconstriction, there is no significant benefit to creatinine clearance over several weeks [19,[30][31][32]. This may be due to the diuretic effect of theophylline mediated through A 1 receptor inhibition.…”
Section: Discussionmentioning
confidence: 92%
“…This is evident by the fact that TAC trough levels of 5 ng/ml are associated with a 5% risk of nephrotoxicity but 50% risk of rejection, while at trough levels of 25ng/ml there is almost no risk of rejection but nephrotoxicity rose to 90% (Burdmann and Bennett, 2008). Both TAC"s blockade of T-cell activation and its most significant side effect; nephrotoxicity are mediated by calcineurin inhibition (McLaughlin et al, 2003). So as long as a high concentration of TAC in the kidney exits and high trough levels are maintained, nephrotoxicity will occur at the cost maintaining efficient immunosuppression.…”
Section: Introductionmentioning
confidence: 88%
“…(McLaughlin et al 2003) Nephrotoxicity of CnIs can be acute or chronic. Acute toxicity is dose-related and is manifested as functional toxicity with acute deterioration of renal function.…”
Section: Introductionmentioning
confidence: 99%